CD19‐targeting chimeric antigen receptor T‐cell therapy is safe and effective for intra‐cardiac B cell non‐Hodgkin lymphoma - Daniel H. Chen; Maeve O'Reilly; Kathleen P. Cheok; Ryan Low; Rajesh Puranik; Samuel Clark; John Malcolm Walker; Charlotte Manisty; Arjun K. Ghosh; Claire Roddie (eJHaem)
Abstract Introduction Chimeric antigen receptor T‐cell (CAR‐T) therapy is highly effective in B‐cell blood cancers, but there is limited data on its safety and efficacy in intra‐cardiac lymphoma, due to the potential risks of cardiotoxicity and pseudo‐progression. Discussion We discuss four high‐risk cases that were managed with a multi‐disciplinary approach, including baseline cardiac risk assessment and surveillance with multimodal cardiac imaging and serum cardiac biomarkers, elective supportive care in the intensive care unit, and early treatment of cytokine release syndrome. Conclusion CAR‐T therapy can be effective and safe in the treatment of B‐cell blood cancers with intra‐cardiac disease.